UEFA Euro 2004 visitors analysis - Ribeiro, J. Cadima (2005)
The purpose of this paper is to establish the profile of the foreign visitor that attended the UEFA Euro 2004 Championship in Portugal, namely in the Minho region. Data were collected through a one-to-one inquiry carried out before the matches that took place in Braga and Guimarães. The survey instrument included aspects like the visitors’ past consumption behaviour, media audience and live attendance sport habits. The results we got show that sport event tourists living in countries with higher per capita income spent more in the UEFA Euro 2004. They also stayed in the country longer than other visitors. Other valuable information for both tourism operators and tournament managers we got is that most sport event tourists decided to overnight on sites with efficient and direct accesses to the matches. Otherwise, they may be characterised as usual sport consumers in terms of active and passive sport consumption behaviour. The return of the visitors to the sites where the UEFA Euro 2004 took place remains unsolved. Future studies should concentrate on community reimbursement and mid/long term benefits.